Culture and portfolios: Trust, precautionary savings and home ownership - Johannes Fleck; Adrian Monninger (European Central Bank (ECB), 2020)
This paper shows that individual beliefs on the effectiveness of formal and informal sources of risk sharing determine financial precautionary behavior. We present empirical evidence demonstrating that higher trust in public insurance systems reduces net liquid wealth while higher trust in communal insurance increases it. This dichotomy is consistent with theories on access to private risk sharing networks. Moreover, we find that both types of trust associate positively with the probability to take on financial risk for the purpose of becoming a homeowner and the related loan-to-value ratio. Our findings are robust across a wide range of econometric controls and specifications.
Keywords: D14; D31; E71; G5; 330; Household Saving; Portfolio Liquidity; Public and Communal Insurance